COVID-19: Putting the general data protection regulation to the test - McLennan, Stuart; Celi, Leo Anthony; Buyx, Alena (JMIR Public Health and Surveillance, 2020)
The coronavirus disease (COVID-19) pandemic is very much a global health issue and requires collaborative, international health research efforts to address it. A valuable source of information for researchers is the large amount of digital health data that are continuously collected by electronic health record systems at health care organizations. The European Union’s General Data Protection Regulation (GDPR) will be the key legal framework with regard to using and sharing European digital health data for research purposes. However, concerns persist that the GDPR has made many organizations very risk-averse in terms of data sharing, even if the regulation permits such sharing. Health care organizations focusing on individual risk minimization threaten to undermine COVID-19 research efforts. In our opinion, there is an ethical obligation to use the research exemption clause of the GDPR during the COVID-19 pandemic to support global collaborative health research efforts. Solidarity is a European value, and here is a chance to exemplify it by using the GDPR regulatory framework in a way that does not hinder but actually fosters solidarity during the COVID-19 pandemic.
CRIS-Team Scopus Importer:2023-03-08
Keywords: COVID-19; Data sharing; Digital health; EHR; Electronic health records; GDPR; Global health; Public health; Research; Research exemption